Cardiovascular risk factors associated with blood metabolite concentrations and their alterations during a 4-year period in a population-based cohort - Lacruz, Maria Elena; Kluttig, Alexander; Tiller, Daniel; Medenwald, Daniel; Giegling, Ina; Rujescu, Dan; Prehn, Cornelia; Adamski, Jerzy; Frantz, Stefan; Greiser, Karin Halina; Emeny, Rebecca Thwing; Kastenmüller, Gabi; et al. (Circulation. Cardiovascular genetics, 2016)
acylcarnitines; amino acids; cardiovascular disease; lifestyle; lipids; metabolomics
"Originally published October 26, 2016"